INFLUENCE OF GAMMA IRRADIATION ON SHELF LIFE AND PROXIMATE ANALYSIS OF FRESH TOMATOES (SOLANUM LYCOPERSICUM) - N. Munir; A. Manzoor; R. Haq; S. Naz (Journal of Animal and Plant Sciences, 2018)
Tomato (Solanum lycopersicum) from the family Solanaceae is the one of the most important and readily consumed fresh vegetable of the world. In tomato, post-harvest quality loss and shelf life is a problem of great concern. The shelf life of tomato is very less as the rottening starts within one week after the harvest. Therefore, it is very important to find out an effective means for increasing the shelf life of tomatoes. Gamma radiation is an important sterilization method to eradicate diverse bacteria and fungi that cause rottening of fruits and vegetables without affecting their nutritional components. The present research was conducted to optimize the gamma radiation dose for tomatoes that did not affect the nutritional value of tomatoes. On the basis of increased shelf life as well as proximate analysis of radiated and non- radiated tomatoes it can be suggested that 1kGyis optimum dose for tomatoes. The treatment of samples with 1kGy had no significant effect on nutritional composition, texture, color and firmness of tomatoes and also helps to increase the shelf life of tomatoes. period of 4-7days is an efficient means of storing the
Keywords: Gamma irradiation; proximate analysis; post-harvest losses; sterilization.